Self-Assembled Bismuth Oxide Microrods Prepared by a Facile Chemical Method - Chokprasombat, Komkrich; Boonyang, Upsorn (Science Essence Journal, 2022)
Bismuth oxides (Bi2O3) are of interest because of their suitable band gaps for photocatalytic activity. Herein, a-Bi2O3 microrods were synthesized by a facile chemical method, and were characterized by X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDS), scanning electron microscope (SEM), and UV-Vis diffuse reflectance spectroscopy (UV-Vis DRS). The results showed that the particles were rod-shaped with lengths in the range of 5-10 mm. Crystalline structure of the particles was monoclinic, and the band gap was around 2.88 eV. When citric acid was used in the synthesis, the bismuth oxide microrods can self-assemble into the hierarchical flower-like structures leading to the alteration of band gap. This self-assembled a-Bi2O3 microstructure can be employed as a photocatalyst with alterable band gap.